Sustainability Practices In National Defence University of Malaysia - Mazura Hj. Mohaiyadin, Norlaila; Mardzuki, Khairunnisa; Saayah Ismail, Amnah; Al-Banna Mohamed, Hasan; Yaacob, Safar; Ong Hai Liaw, Jessica (International Journal of Engineering and Technology, 2018)
The aims of this study are to investigate the level of sustainability practices items in each dimension; either the most common or least common practices and to investigate the level of overall sustainability practices that fall under high, medium or lower common practices in National Defence University of Malaysia (NDUM). A sample of 188 respondents from administration, selected faculties and centres of NDUM participated in responding to the survey of this study. Researchers used descriptive analysis from the Statistical Package for the Social Sciences software. Results found that there are common and least common sustainability practices in each dimension, and they have similarities and differences in terms of findings with previous literatures. Results also found that the sustainability practices for all dimensions are at a medium level. The results of this study will contribute to the awareness of sustainability practices among members of the university and to add to the literature review in the field of sustainability issues.Â